Effects of iron oxide nanoparticles: Cytotoxicity, genotoxicity, developmental toxicity, and neurotoxicity - Valdiglesias, V. (2018)
Iron oxide nanoparticles (ION) with superparamagnetic properties hold great promise for use in various biomedical applications; specific examples include use as contrast agents for magnetic resonance imaging, in targeted drug delivery, and for induced hyperthermia cancer treatments. Increasing potential applications raise concerns over their potential effects on human health. Nevertheless, very little is currently known about the toxicity associated with exposure to these nanoparticles at different levels of biological organization. This article provides an overview of recent studies evaluating ION cytotoxicity, genotoxicity, developmental toxicity and neurotoxicity. Although the results of these studies are sometimes controversial, they generally indicate that surface coatings and particle size seem to be crucial for the observed ION-induced effects, as they are critical determinants of cellular responses and intensity of effects, and influence potential mechanisms of toxicity. The studies also suggest that some ION are safe for certain biomedical applications, while other uses need to be considered more carefully. Overall, the available studies provide insufficient evidence to fully assess the potential risks for human health related to ION exposure. Additional research in this area is required including studies on potential long-term effects.